The Relationship Between Organizational Culture and Work Environment on Employee Performance at the Bogor City Regional General Hospital - Abdurachman, Gini Gantini; Agung, Syahrum; Kusuma, Anuraga (prodima@fe.uika-bogor.ac.id, 2024)
This research aims to determine the relationship between organizational culture and the work environment on employee performance. This research was carried out by distributing questionnaires to 93 employees at the Bogor City Regional General Hospital, processed using the SPSS 25 application with the Spearman rank analysis method showing that the relationship between the two variables, namely organizational culture and employee performance, has a relationship that destroys the numbers with a significance of 0.001 which is less. of 0.05 To see the correlation between the two variables, look at the number 0.696 which means